2000
DOI: 10.1002/1097-4571(2000)9999:9999<::aid-asi1046>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Connecting minds: Computer-mediated communication and scientific work

Abstract: This article summarizes the preliminary findings from a recent study of scientists in four disciplines with regard to computer‐mediated communication (CMC) use and effects. Based on surveys from 333 scientists, we find that CMC use is central to both professional and research‐related aspects of scientific work, and that this use differs by field. We find that e‐mail use focuses on coordination activities, and its biggest effect is helping to integrate scientists into professional networks. We do not find gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 17 publications
3
65
0
3
Order By: Relevance
“…The greatest benefit seemed to be facilitation of scientific communication, providing the glue for the 'virtual college'. 13 Katz and Martin noted that one of the reasons for increasing collaboration was the growing importance of interdisciplinary fields. They suggested that:…”
Section: Communication and Collaborationmentioning
confidence: 98%
“…The greatest benefit seemed to be facilitation of scientific communication, providing the glue for the 'virtual college'. 13 Katz and Martin noted that one of the reasons for increasing collaboration was the growing importance of interdisciplinary fields. They suggested that:…”
Section: Communication and Collaborationmentioning
confidence: 98%
“…One open question regarding collaboratories is the degree to which they can change the nature of this relationship between propinquity and propensity to collaborate. Evidence from a limited set of studies suggest that there is a positive relationship between email usage and remote collaboration (Cohen, 1996;Walsh & Bayma, 1996;Walsh, Kucker, & Maloney, 2000;Walsh & Maloney, 2002), but this question remains to be definitively answered. Hara, et al (2003) (Watson, 1968), but these do not likely represent the modal experience of scientists in collaborations.…”
Section: General Studies Of Scientific Collaborationmentioning
confidence: 99%
“…Several arguments support a productivity rise: In general, more information is available over computer networks and the search and retrieval of information is faster (NENTWICH, 2003). Access to remote instruments and data sets is also easier and faster (WALSH et al, 2000). Research may become better connected and more modular (KIRCZ, 1998;347 NENTWICH, 2003).…”
Section: What Do We Know About Research Productivity At the Individuamentioning
confidence: 99%